2019
DOI: 10.1136/bmjopen-2019-030772
|View full text |Cite
|
Sign up to set email alerts
|

Simple risk score based on the China Acute Myocardial Infarction registry for predicting in-hospital mortality among patients with non-ST-segment elevation myocardial infarction: results of a prospective observational cohort study

Abstract: ObjectivesTo simplify our previous risk score for predicting the in-hospital mortality risk in patients with non-ST-segment elevation myocardial infarction (NSTEMI) by dropping laboratory data.DesignProspective cohort.SettingMulticentre, 108 hospitals across three levels in China.ParticipantsA total of 5775 patients with NSTEMI enrolled in the China Acute Myocardial Infarction (CAMI) registry.Primary outcome measuresIn-hospital mortality.ResultsThe simplified CAMI-NSTEMI (SCAMI-NSTEMI) score includes the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…To address the limitations mentioned above, the CRM was developed to predict in-hospital mortality, particularly for Chinese NSTEMI patients, and its diagnostic performance was superior to that of the GRM in two internal validation studies using data from CAMI registry [ 8 , 9 ]. Our effort further extended this conclusion in an external validation cohort by indicating a larger AUC, positive NRI, and less disagreement between the observed and predicted mortality for the CRM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the limitations mentioned above, the CRM was developed to predict in-hospital mortality, particularly for Chinese NSTEMI patients, and its diagnostic performance was superior to that of the GRM in two internal validation studies using data from CAMI registry [ 8 , 9 ]. Our effort further extended this conclusion in an external validation cohort by indicating a larger AUC, positive NRI, and less disagreement between the observed and predicted mortality for the CRM.…”
Section: Discussionmentioning
confidence: 99%
“…To diminish the impact of this paradox, the current guidelines consider the risk assessment by the Global Registry of Acute Coronary Events (GRACE) risk model as a fundamental component to select the most appropriate therapeutic strategy for NSTEMI patients [ 1 3 ]. However, several observations have suggested that the performance of the GRACE risk model (GRM) was unsatisfactory among Chinese NSTEMI patients [ 8 , 9 ]. Recently, a novel risk model has been developed for the risk evaluation of NSTEMI patients [ 8 ] based on multicenter data from the China Acute Myocardial Infarction (CAMI) registry [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of blood glucose in the context of MI is complex, involving both protective and deleterious effects on the myocardium 29 . This may explain why blood glucose was not included in the GRACE or CAMI risk scores 10,30 …”
Section: Discussionmentioning
confidence: 99%
“…29 This may explain why blood glucose was not included in the GRACE or CAMI risk scores. 10,30 Pulmonary hypertension is frequently observed following AMI, 31 and elevated PASP after AMI is often associated with poor prognosis. 32,33 Indeed, PASP was proved to be a strong independent predictor of short-term death in a previous study.…”
Section: Discussionmentioning
confidence: 99%